Using advanced manufacturing technology for smarter construction. Issue 4 (7th June 2019) - Griffin, Allan; Hughes, Ruby; Freeman, Chris; Illingworth, James; Hodgson, Tomas; Lewis, Michael; Perez, Ejae
Abstract : Productivity in the UK construction sector has historically lagged behind other industry sectors. The government is aiming to improve this through increasing the level of pre-manufactured value in built assets. Since 2001, the University of Sheffield's Advanced Manufacturing Research Centre has been developing technological innovations for the aerospace and automotive sectors. This paper shows how lessons learnt from, and technologies developed for, these sectors can be transferred into the construction supply chain through horizontal innovation. Technologies such as robotics and automation, augmented and virtual reality, discrete event simulation, large volume metrology, and improved tools and processes all have a role to play. Significant productivity increases are possible, with the benefit often driven by the digitalisation of traditionally manual paper-based processes.